Tregitope-linked Refined Allergen Vaccines for Immunotherapy in Cockroach Allergy. Issue 1 (December 2018) - Prangtaworn, Pannathee; Chaisri, Urai; Seesuay, Watee; Mahasongkram, Kodchakorn; Onlamoon, Nattawat; Reamtong, Onrapak; Tungtrongchitr, Anchalee; Indrawattana, Nitaya; Chaicumpa, Wanpen; Sookrung, Nitat
Abstract Allergen-specific immunotherapy (AIT) facilitates long-term resolution of allergic morbidity resulting in reduced drug use and increased refractoriness to new sensitization. AIT effectiveness has been demonstrated in seasonal and perennial allergies, and insect stings. However, data and studies in AIT relative to cockroach (CR) allergy are relatively scarce. In this study, mice allergic to American CR (Periplaneta americana ) were treated with a liposome (L)-entrapped vaccine made of mouse Tregitope289-Per a 9 of the CR, Tregitope167-Per a 9, or Per a 9 alone – or placebo. Allergic mice that received an individual vaccine intranasally had reduced Th2 response, reduced lung inflammation, and reduced respiratory tissue remodeling. However, only L-Tregitope289-Per a 9 and L-Tregitope167-Per a 9 induced expression of immunosuppressive cytokine genes (IL-10, TGF-β, andIL-35 for L-Tregitope289-Per a 9, andIL-10 andTGF-β for L-Tregitope167-Per a 9) and increment of idoleamine-2, 3-dioxygenase 1 (IDO1), indicating that these vaccines caused allergic disease suppression and reversal of respiratory tissue remodeling via generation of regulatory lymphocytes. Liposome entrapped-recombinant Per a 9 (L-Per a 9) did not cause upregulation of immunosuppressive cytokine genes and IDO1 increment; rather, L-Per a 9 induced high expression ofIFN-γ in lungs of treated mice, which resulted in mitigation of allergic manifestations. This study provides compelling evidence that both liposome-entrapped vaccines made of single refined major allergen alone and single refined major allergen linked with Tregitopes are effective for reducing allergen-mediated respiratory tissue inflammation and remodeling, but through different mechanisms.